Systemic inflammation response index as a prognostic predictor in patients with acute ischemic stroke: A propensity score matching analysis - Dang, Hui; Mao, Wenjuan; Wang, Shanshan; Sha, Jing; Lu, Mingjia; Cong, Li; Meng, Xuegang; Li, Hongyan (Frontiers in Neurology, 2023)
Background: Acute Ischemic Stroke (AIS), the most common type of stroke, is a major cause of morbidity and mortality worldwide. A growing number of studies have demonstrated that inflammation is the critical mechanism in AIS. Being an easily available and effective inflammatory marker, systemic inflammation response index (SIRI) shows a high association with mortality in patients with cancer and intracerebral hemorrhage. In this study, we evaluated the potential prognostic role of SIRI in critically ill patients with AIS. Methods: Clinic data was extracted from the Medical Information Mart data for Intensive Care IV (MIMIC-IV) database. The optimal cut-off value of SIRI was determined by X-tile software. The primary outcome was 90-day all-cause mortality, and the secondary outcomes were the 30-day and 1-year all-cause mortality of AIS patients. Cox proportional hazards regression analyses were used to assess the association between SIRI levels and all-cause mortality, and survival curves were estimated using the Kaplan–Meier method. Further, a 1:1 propensity score matching (PSM) method was performed to balance the influence of potential confounding factors. Results: A total of 2043 patients were included in our study. The X-tile software indicated that the optimal cut-off value of the SIRI for 90-day mortality was 4.57. After PSM, 444 pairs of score-matched patients were generated. Multivariate cox proportional hazard model showed that after adjusting for possible confounders, high SIRI level (≥ 4.57) was independently associated with the 90-day all-cause mortality before PSM cohort (HR = 1.56, 95% CI: 1.30-1.89, p < 0.001) and the PSM subset (HR = 1.47, 95% CI: 1.16-1.86, p = 0.001). Survival curves showed that patients with SIRI ≥ 4.57 had a significantly lower 90-day survival rate before PSM cohort (56.7% vs. 77.3%, p <0.001) and the PSM subset (61.0% vs. 71.8%, p = 0.001). Consistently, AIS patients with high SIRI level (≥ 4.57) still presented a significantly high risk of 30-day and 1-year all-cause mortality before and after PSM. Conclusions: Higher SIRI (≥ 4.57) was associated with a higher risk of 90-day, 30-day, and 1-year mortality and can serve as a prognostic predictor of mortality in patients with acute ischemic stroke patients.